Local Indigenous: Internalization of Siri And Kareso Tamatappuk on Teacher Performance - Torro, Supriadi; Indah, Sukma; Sunra, La; Ario Sumilih, Dimas; Ismail, Ashari (KnE Social Sciences, 2024)
This research aims to determine: 1) Internalization of siri’ on teacher performance. 2) Internalization of kareso tamatappuk on teacher performance. 3) Internalization of siri ’ and kareso tamatappuk on teacher performance. This research was conducted with a quantitative approach, with a population of 52 for research sampling. The data collection technique used a questionnaire with a Likert scale, each of which has been tested and meets the requirements of validity and reliability. The data analysis techniques used were simple linear regression and multiple linear regression. The research results show that: 1) Siri’s internalization influences teacher performance. Based on simple linear regression analysis with a coefficient value of 0.247, the results of the t test with a calculated t value is 2.637 > ttable value of 2.010, a significance value of 0.001 <0.05, and an r squared value of 37.1%. 2) Internalization of kareso tamatappuk has an effect on teacher performance at SMA Negeri 19 Gowa Regency. Based on simple linear regression analysis with a coefficient value of 0.412, the t test results with a tcount value of 2.801 > t table value of 2.010, a significance value of 0.003 <0.05, and an r squared value of 39.4 %. 3) Internalization of Siri’ and kareso tamatappuk influences teacher performance, with the amount of influence exerted is around 45.1 %. Keywords: Siri’ internalization, Kareso Tamatappuk, teacher performance